An encyclopedia of swearing : the social history of oaths, profanity, foul language, and ethnic slurs in the English-speaking world /: the social history of oaths, profanity, foul language, and ethnic slurs in the English-speaking world. (2015) - Hughes, Geoffrey, 1939-
No abstract available